2017
DOI: 10.1177/0954407017694412
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical degradation tests on a carbon-black-filled ethylene propylene diene monomer rubber under tensile strain

Abstract: Rubber hoses play an important role as a path for carrying the coolant liquid between the radiator and the automotive engine. However, the rubber hoses are apt to deteriorate because of the formation of a galvanic circuit between the rubber hose, the coolant water and the fitting metal part of the engine. Such electrochemical degradation can damage the inner skin of the hose in contact with the coolant liquid heated by the working engine, which often leads to leakage of the coolant water and thereby to hose fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In this study, composites E and F were prepared using a peroxide vulcanization system, forming stronger carboncarbon bonds instead of the weaker sulfur–sulfur linkages 1 . HO2 anions struggle to attack these robust carbon–carbon cross‐links, reducing the likelihood of crack formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, composites E and F were prepared using a peroxide vulcanization system, forming stronger carboncarbon bonds instead of the weaker sulfur–sulfur linkages 1 . HO2 anions struggle to attack these robust carbon–carbon cross‐links, reducing the likelihood of crack formation.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been a notable surge in the development of EPDM rubber composites for automotive applications, especially in the production of hoses for coolant transportation. However, these composites encounter challenges related to electrochemical degradation (ECD) stemming from the formation of galvanic cells and subsequent redox reactions within the material 1 . Despite extensive research on the physico‐mechanical properties of EPDM composites, studies specifically targeting ECD prevention are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of rubber degradation in automotive components has been reported in the literature such as car wiper rubber blade [5], rubber hoses for car radiators [6] and engine rubber mounting [7]. There are also many studies undertaken on fatigue damage on rubbers materials.…”
Section: Introductionmentioning
confidence: 99%